Success Factors On Joint Venture Projects For Indigenuous Bumiputera Contractors In Malaysia - Adnan, H.; Kassim, A.; Chong, Heap Yih (IMS Inet Publication, 2012)
The survey found a consensus of opinion which identifies seven (7) factors of success and eight (8) factors of failure of Joint venture through questionnaires survey to the 100 of indigenious Bumiputera Contractors Class ‘A’ which is locally incorporated and registered by the Malaysian Construction Industry Development Board. Success factors such as agreement of contract terms, commitment, management control, inter-partner trust, cooperation, financial stability, criteria partner selection, profit, equity control, mutual understanding, partner’s experience and cultural understanding were considered critical and were significant from this research. The findings of this research significantly enhance and build upon existing levels of knowledge and understanding in knowledge-based management practices and organisational culture which influences project-based joint venture within the construction industry. When applied to a JV project in Malaysia will actively contribute to a profitable conclusion for one or more of the parties involved. These are considered to be the ‘Critical Factors Affecting JV’ projects in Malaysia. The result of this study is expected to provide useful guidelines for forming and implement efficient, effective joint venture in Malaysia and in other similar strategic alliance and to improve these venture prospects for success.